Genetically predicted basal metabolic rate and venous thromboembolism risk: a Mendelian randomization study - Huang, Jian; Xie, Yubo (Frontiers in Nutrition, 2023)
Background: Basal metabolic rate (BMR) is the minimum amount of energy needed by the body to carry out essential physiological functions. The goal of this study was to evaluate whether BMR causally influences venous thromboembolism (VTE) and its subtypes in European individuals.Methods: A two-sample Mendelian randomization (MR) was performed. Within a genome-wide association study (GWAS) involving 454,874 people, genetic variants were chosen as instrumental variables based on their significant associations (P<5× 10 − 8 ) with BMR and their limited linkage disequilibrium (r2<0.001). The FinnGen project served as sources for summary statistics of VTE, encompassing different subtypes.Results: Using the multiplicative random-effect inverse variance weighted method, our investigation revealed that one standard deviation higher BMR was associated with VTE (odds ratio [OR]=1.684, 95% confidence interval [CI]: 1.465-1.936, P=2.339×10 -13 ), PE (OR=1.824, 95% CI: 1.512-2.200, P=3.399×10 -10 ), and DVT of lower extremities (OR=1.887, 95% CI: 1.562-2.280, P=4.778 × 10 -11 ). The consistency of these associations was observed in sensitivity analyses using various MR techniques like Mendelian randomization pleiotropy residual sum and outlier, MR-Egger, weighted median, and contamination mixture method. In addition, multivariable MR revealed direct effects of BMR on VTE and its subtypes when taking body mass index and current tobacco smoking into account.Higher BMR may increase the risk of VTE and its subtypes including PE and DVT of lower extremities.